Carotenoid Intake and Circulating Carotenoids Are Inversely Associated with the Risk of Bladder Cancer: A Dose-Response Meta-analysis. Issue 3 (4th December 2019) - Wu, Shenghui; Liu, Yanning; Michalek, Joel E; Mesa, Ruben A; Parma, Dorothy Long; Rodriguez, Ronald; Mansour, Ahmed M; Svatek, Robert; Tucker, Thomas C; Ramirez, Amelie G
ABSTRACT: Some evidence indicates that carotenoids may reduce the risk of bladder cancer (BC), but the association is unclear. We conducted a systematic review and meta-analysis of case-control and cohort studies investigating the relation between carotenoid intake or circulating carotenoid concentrations and BC risk in men and women. All relevant epidemiologic studies were identified by a search of PubMed and Scopus databases, and the Cochrane Library from inception to April 2019 with no restrictions. A random-effects model was used to calculate pooled RRs and their 95% CIs across studies for high compared with low categories of intake or circulating concentrations. We also performed a dose-response meta-analysis using the Greenland and Longnecker method and random-effects models. A total of 22 studies involving 516, 740 adults were included in the meta-analysis. The pooled RRs of BC for the highest compared with the lowest category of carotenoid intake and circulating carotenoid concentrations were 0.88 (95% CI: 0.76, 1.03) and 0.36 (95% CI: 0.12, 1.07), respectively. The pooled RR of BC for the highest compared with lowest circulating lutein and zeaxanthin concentrations was 0.53 (95% CI: 0.33, 0.84). Dose-response analysis showed that BC risk decreased by 42% for every 1 mg increase in daily dietary β-cryptoxanthin intake (RR: 0.58; 95% CI: 0.36, 0.94); by 76% for every 1 μmol/L increase in circulating concentration of α-carotene (RR: 0.24; 95% CI: 0.08, 0.67); by 27% for every 1 μmol/L increase in circulating concentration of β-carotene (RR: 0.73; 95% CI: 0.57, 0.94); and by 56% for every 1 μmol/L increase in circulating concentrations of lutein and zeaxanthin (RR: 0.44; 95% CI: 0.28, 0.67). Dietary β-cryptoxanthin intake and circulating concentrations of α-carotene, β-carotene, and lutein and zeaxanthin were inversely associated with BC risk. The protocol was registered at PROSPERO as CRD42019133240.